Feasibility of E-learning Textbooks of Item Analysis Material to Improve Student Competence - Hari Sugiharto Setyaedhi; Atan Pramana (Jurnal Edutech Undiksha, 2024)
The development of e-learning textbooks of learning assessment with items analysis material is based on the fact that there is still a lack of lecturers in developing textbooks that are implemented in virtual learning. This causes students to become less interested in learning, causing a decrease in student learning outcomes. The development of textbooks with e-learning aims to fulfill textbooks that can be accessed through Vinesa so that students can access the textbooks anytime and anywhere, so it is expected that the competence of student learning outcomes can increase. The analysis uses quantitative descriptive techniques. The target of this study was 90 students. Data were obtained through observation, interviews, questionnaires, and tests. Development research using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The feasibility results of e-learning textbook development for Learning Assessment are declared feasible by a) the results of material validation were very feasible (91%), b) the results of learning material validation were very feasible (90%) c) the results of learning media validation were very feasible (94%) d) the results of language validation were very feasible (90%), e) the results of individual trials were very feasible (80%), f) the results of small group trials were very feasible (83%). This study concludes that the development of e-learning textbooks for Learning Assessment with items analysis material was very feasible to be used to improve student competence and deserves to be used as the availability of learning resources that are limited in time and place.